Analisis Kebijakan Penanaman Modal dalam Mewujudkan Iklim Investasi yang Kondusif di Kota Semarang - Herlambang Lutfi Prakoso; Charis Christiani (Universitas 17 Agustus 1945, 2025)
This study aims to analyze the investment policies in Semarang City, focusing on Regional Regulation Number 9 of 2014 and its execution by the Investment and One-Stop Integrated Services Office (DPMPTSP). Using a descriptive qualitative approach, this research applies the policy implementation theory by Edward III, examining four variables: communication, resources, disposition, and bureaucratic structure. The results show that despite significant efforts to promote investment, the policy implementation still faces various challenges. These include suboptimal communication between agencies, limited human resources (HR) capacity, and misalignment between regional regulations and newer national policies, such as the Omnibus Law and the Online Single Submission (OSS) system. Although Semarang City has great investment potential supported by adequate infrastructure, the realized investment has yet to meet the set targets. Therefore, this study recommends an optimization strategy that includes simplifying licensing procedures, enhancing the capacity of apparatus, harmonizing regulations across government levels, and integrating technology to improve transparency and ease of investment.